The novel ZmTCP7 transcription factor targets AGPase-encoding gene ZmBt2 to regulate storage starch accumulation in maize - Ajayo, Babatope Samuel; Li, Yangping; Wang, Yayun; Dai, Chengdong; Gao, Lei; Liu, Hanmei; Yu, Guowu; Zhang, Junjie; Huang, Yubi; Hu, Yufeng (Frontiers in Plant Science, 2022)
The process of starch biosynthesis is a major developmental event that affects the final grain yield and in maize (Zea mays L.), and transcriptional regulation plays a key role in modulating the expression of the main players in the pathway. ZmBt2, which encodes the small subunits of AGPase, is a rate-controlling gene of the pathway; however, much remains unknown about its transcriptional regulation. Our earlier study identifies a short functional fragment of ZmBt2 promoter (394-bp), and further shows it contains multiple putative cis-acting regulatory elements, demonstrating that several transcription factors may govern ZmBt2 expression. Here, we identified a novel TCP transcription factor (TF), ZmTCP7, that interacted with the functional fragment of the ZmBt2 promoter in a yeast one hybrid screening system. We further showed that ZmTCP7 is a non-autonomous TF targeted to the nucleus and predominantly expressed in maize endosperm. Using promoter deletion analyzes by transient expression in maize endosperm protoplasts combined with electrophoretic mobility shift assays, we found that ZmTCP7 bound to GAACCCCAC elements on the ZmBt2 promoter to suppress its expression. Transgenic overexpression of ZmTCP7 in maize caused a significant repression of ZmBt2 transcription by approximately 77.58%, resulting in a 21.51% decrease in AGPase activity and a 9.58% reduction in the endosperm starch content of transgenic maize. Moreover, the expressions of ZmBt1, ZmSSI, ZmSSIIa and ZmSSIIIa were increased, while those of ZmSh2 and ZmSSIV reduced significantly in the endosperm of the transgenic maize. Overall, this study shows that ZmTCP7 functions as a transcriptional repressor of ZmBt2 and a negative regulator of endosperm starch accumulation, providing new insights into the regulatory networks that govern ZmBt2 expression and starch biosynthesis pathway in maize.